Study of Deformation Behavior of Retaining Walls at Sepakat Ii Parallel Road Project in Pontianak City - Siregar, Novita Januarti Siregar; Eka, Priadi; Aprianto, Aprianto; Rustamaji, R M; Bachtiar, Vivi (Jurnal Inovasi Teknologi, 2023)
The development of urban planning and infrastructure such as roads, buildings, bridges, ports has increased in recent years in Pontianak City. One of them is the construction of Jalan Parallel Sepakat II which was carried out in early 2022, connecting Jalan Sepakat II to the Tanjungpura University Campus Complex. In the case in the field, the previously compacted embankment has decreased, so backfilling is carried out to adjust the planned elevation. Due to the unsafe existing condition factor, improvements were made that were supported by retaining wall modeling. In addition to the retaining wall modeling, the current planning in the field is also stabilized by using a pile and geotextile, in order to increase the bearing capacity of the soil and can minimize the decrease or deformation that occurs at the research location. In the process of analyzing the retaining wall, analysis is also carried out with the Plaxis Proffesional 8.6 program. The results obtained in the form of deformation numbers and safety factor results. From the conclusion, the factor of safety is obtained which is not safe so that it is feasible to be reinforced. However, some adjustments are needed to the design plan so that it can function properly in accordance with the intent and purpose of the reinforcement.